A new species of Ophiocordyceps (Ophiocordycipitaceae) from Mizoram, India - Chawngthu, Zohmangaiha; Vabeikhokhei, Josiah Mc; Zomuanpuii, Rita; Mandal, Surajit De; Zothanzama, John (Phytotaxa, 2021)
Ophiocordyceps mizoramensisis described as a new species from Mizoram by using a combination of morphological and molecular phylogenetic analysis. The molecular phylogenetic analysis include both the subunits (LSU and SSU), the internal transcribed spacers (ITS1 and ITS2) with the 5.8S gene region, along with Tef (Translation elongation factor). The new species Ophiocordyceps mizoramensis, differs from other closely related species based on molecular phylogenetic relationships, genetic distance, and minor morphological characters related to sexual structures. The entomopathogenic Ophiocordyceps mizoramensis infected the host Polistes olivaceus (paper wasp) causing death to the whole colony of the hive.